Pengembangan Video Tutorial Pembelajaran Badminton Universitas Jambi - Muhammad Ali; David Iqroni (Universitas Batanghari Jambi, 2022)
This study aims to develop videos of basic badminton technical skills as a learning medium for badminton athletes. This research is a research and development research and development (R&D). This research was conducted in several steps, namely: Potential and Problems, Data Collection, Product Design, Design Validation, Design Revision, Product Trial, Product Revision, Usage Trial, Product Revision, Mass Production. Validation was carried out by media experts and media experts. The population in this study was badminton athletes PB. Boy Junior Kuala Tungkal with a total of 5 athletes for small group trials and 10 athletes for large group trials. The results of the research on the development of the Jambi University Badminton Learning Video Tutorials are worthy of being used as learning media with the 'Very Good' category. This can be seen from the results of research from material experts 91% and media experts 94% as well as large group trials of 88%, and small group trials of 76% with the